Finite element study on the initiation of new fractures in temporary plugging fracturing - Xing, Xuesong; Wu, Guangai; Zhou, Jun; Zhang, Anshun; Hou, Yanan; Xie, Xin; Wu, Jianshu; Kong, Xiangwei; Li, Song (Frontiers in Physics, 2023)
Hydraulic fracturing technology is an important means to efficiently exploit unconventional oil and gas reservoirs. As development of oil and gas fields continues at a high rate, the life cycle of oil and gas wells has been significantly shortened. Fracture sealing is often used to transform oil and gas reservoirs, maintaining long-term economic development benefits. Multiple high conductivity channels were created between the borehole and the reservoir through temporary sealing of fractures near the contaminated zone. This extended the recovery range and further improved the recovery of oil and gas. A mathematical model was developed to predict the distribution of stress around the artificial fracture prior to the rupture of the seal. Finite element software was used to model the stress distribution around a reservoir containing both natural and artificial fractures. We discuss the mechanical conditions for the initiation of a new fracture and the optimal timing for fracture sealing. The prediction of the propagation and propagation trajectories of the new fracture is revealed, and the behavior rules for the initiation and steering propagation of the new fracture are clarified. These results can facilitate theoretical studies and on-site technical optimization of fracture sealing.